Armchair warriors : private citizens, popular press, and the rise of American power - Davidson, Joel R. (Joel Robert), 1959- (Naval Institute Press, 2014)
This book is a history of public information and personal ideas about war and the military over the last century. It examines the interplay between popular media coverage of the nation's wars and the perceptions of ordinary Americans regarding military issues. Davidson studied Americans who produced a wealth of proposals to solve some of the most pressing military problems of their day. His book consists of hundreds of letters sent to those in charge of the armed forces, advising them on issues ranging from grand strategy to individual combat. Davidson sets their letters alongside extract.